Congenital cholesteatoma clinical and surgical management. (January 2023) - Wei, Bo; Zhou, Peng; Zheng, Yongbo; Zhao, Yu; Li, Tianjun; Zheng, Yan
Abstract: Objectives: Congenital cholesteatoma (CC) is accompanied by hearing loss and an intact tympanic membrane. However, the hearing loss is usually associated with otitis media, and the diagnosis of CC is frequently delayed in patients with an intact tympanic membrane. This study aimed to describe the clinical characteristics, management and outcomes of patients with CC. Methods: We reviewed patients with cholesteatoma from January 2011 to May 2020 and selected those meeting the congenital cholesteatoma criteria. The primary outcome measures included presenting symptoms, surgical findings, stage of disease, recurrence rate and hearing outcomes. Results: We reviewed 1646 medical files of cholesteatoma patients and identified 18 patients with congenital cholesteatoma, the mean age at operation was 8.13 ± 1.36 years (range 3–18). The unilateral hearing loss included moderate 13 patients (72.2%), severe 4 patients (22.2%), and slight 1 (5.6%). There were 14 cases of conductive hearing loss (77.8%) and 4 cases of mixed hearing loss (22.2%). The mean course of disease was 1.41 ± 0.05 years (range 0.4–3). The surgical management was oto-endoscope exploratory tympanotomy in 1（5.6%）, canal wall up mastoidectomy in 12 (66.7%) and canal wall down in 5 (27.8%), with 17 (94.4%) ossicular replacements. Seventeen (94.4%) patients presented with Potsic stage III-IV. Recurrence occurred in 5.6% of patients in stage III and 11.1% of patients in stage IV. After surgery, patients achieved normal voice tone hearing. Conclusions: To diagnose it early, congenital cholesteatoma should be considered as a possible aetiology for hearing loss patients with an intact tympanic membrane. In our study, most patients were diagnosed at III and IV stage. This highlights the need to promote awareness of the disease among primary physicians in the community healthcare system. Surgical management with removal of the cholesteatoma and reconstruction of the tympanum and ossicular chain is an effective treatment. Highlights: In congenital cholesteatoma patients, the mean age at operation was 8.13 ± 1.36 years (range 3–18), mean course of disease was 1.41 ± 0.05 years (range 0.4–3). Seventeen (94.4%) patients presented with Potsic stage III-IV. After surgery, congenital cholesteatoma patients obtained normal voice tone hearing.